THE RELATIONSHIP BETWEEN SELF-AFFICACY AND STUDENTS' LEARNING MOTIVATION WITH LEARNING INDEPENDENCE OF CLASS VIII STUDENTS OF SMP AD DUROH MEDAN MARELAN - Sri Rahayu; Amanah Surbakti; Risydah Fadhilah (RADJA PUBLIKA, 2023)
The research objective was to determine the relationship between self-efficacy and learning independence for Grade VIII students of SMP Ad Duroh, Medan Marelan District. To find out the relationship between learning motivation and learning independence for class VIII students of SMP Ad Duroh, Medan Marelan District. To find out the relationship between Academic self-efficacy and learning motivation together with the learning independence of class VIII students of SMP Ad Duroh, Medan Marelan District. research approach, namely quantitative research). This research was conducted in class VIII SMP Ad Duroh, Medan Marelan District, which is located on Jl. Marelan Raya Pasar 4 Barat began on May 25 2023 with a sample of 130 students from a total population of 138 people enrolled in class VIII SMP Ad Durah Medan Marelan. The data collection technique used was a questionnaire distribution method with a Likert scale. The sampling technique used in this study was Proportional Random Sampling. The data analysis technique is multiple linear regression test, reliability test, classic assumption test, hypothesis test. Process the data using the SPSS 25 statistical program for windows. The results showed that there was a relationship between self-efficacy and student learning independence. It was found that the rxy coefficient was 0.449 with p <0.05, this means that the level of self-efficacy students have will be able to increase or decrease the learning independence of class VIII students at SMP Ad durah Medan.